Foucault, Lévinas e Marx em leituras sobre a escola no cuidado de si de pessoas com deficiência - Rangel, Fabiana Alvarenga (2012)
This research aimed to understand the care of the self among people with disabilities into their school lives, with special attention to their subjective formation besides the interposition of the master along that formation and that care. For so, between 2009 and 2010, in a metropolitan city of Espírito Santo, we accomplished semi-structured interviews with two youths with disabilities, their mothers and also their masters of the care; beyond questionnaires applied to different education professionals of their schools. It was a qualitative research which had Michel Foucault, Emmanuel Lévinas and Karl Marx as its theoretical basis. On the thesis development, we observe that the subjective formation of those youths was strongly interfaced by issues historically constructed between education and labor. In the analysis, we understood that school presented itself as a privileged space of the care of the self, having in it a locus of productive subject formation, which is the ideal subject of normality. However, we noted that the accomplishment of the care of the self into school space required the responsible hand of the master of care. Without that hand egoistic man rights appealed to the totality of disability and to the Inclusive Education plenitude in order to refuse the presence of students with disabilities, provoking their faces’ murdering. In this sense, we arrive to the necessity of the transcendence of the normal and abnormal totalities, which would allow the issues that started the thesis to reach the ethics of alterity, besides promote the turning of that subject in a citizen.